2017
DOI: 10.7759/cureus.1514
|View full text |Cite
|
Sign up to set email alerts
|

Management of Tiny Meningiomas: To Resect or Not Resect

Abstract: Meningiomas are most often benign primary intracranial tumors that are frequently found incidentally on imaging. Larger sized meningiomas may present with symptoms such as seizures and headaches. Smaller meningiomas are commonly asymptomatic and usually observed with serial imaging. We present two female patients, both of whom were found to have very small left frontal meningiomas that marginated Broca’s area. The first patient in this case series experienced episodes resembling seizures which consisted of wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Five ECMO studies and eight ECCO2R studies reporting a total of 494 patients were identified (Table 1). All the ECMO studies were retrospective reviews [1,[4][5][6][7] and the ECCO2R studies were mostly case reports, with only one being a case series [3,[8][9][10][11][12][13][14][15]. After exclusions, five ECMO studies and one ECCO2R study were included in total.…”
Section: Resultsmentioning
confidence: 99%
“…Five ECMO studies and eight ECCO2R studies reporting a total of 494 patients were identified (Table 1). All the ECMO studies were retrospective reviews [1,[4][5][6][7] and the ECCO2R studies were mostly case reports, with only one being a case series [3,[8][9][10][11][12][13][14][15]. After exclusions, five ECMO studies and one ECCO2R study were included in total.…”
Section: Resultsmentioning
confidence: 99%